FAKTOR-FAKTOR YANG MEMPENGARUHI TIDAK BERFUNGSINYA PASAR TRADISIONAL (Studi Kasus: Pasar Lamgapang Kecamatan Ulee Kareng Kota Banda Aceh) - Eddy Syahputra; Mochammad Afifuddin; Safwan Yusuf (Prodi Magister Teknik Sipil Unsyiah, 2018)
Lamgapang Market is one of the traditional markets located in Gampong Lamgapang, Ulee Kareng Sub-district, Banda Aceh City. The traditional market of Lamgapang was built in 2008 by the Rehabilitation and Reconstruction Agency (BRR). After completion in 2009 the Department of Cooperatives UKM and Trade Banda Aceh City has been functioning this market Lamgapang, but only operates for 6 months due to not many visitors/buyers. Therefore traders no longer sell in the market Lamgapang and back to where they started selling Ulee Kareng market. This study aims to identify factors that may affect the non-functioning of traditional markets Lamgapang, and identify the form of market Lamgapang desired by buyers and traders. This research uses qualitative method through observation and interview, and quantitative method through questionnaires distribution. The number of respondents in this study is 163 people. Statistical analysis used in data processing consists of validity and reliability test, while data analysis is used descriptive analysis, using the aid of Statistical Product and Service Solution (SPSS) version 22 software. The results show that the factors that influence the malfunction of Lamgapang market is the location of the market is not strategic, the lack of traders remain, there are still street vendors selling in the old market, accessibility that is difficult to reach, lonely buyers, and lanes of traffic away from the crowd. The market shape of Lamgapang that is highly desirable by buyers and traders is that it lies in a strategic position, frequented by buyers, many street vendors, easily accessible via a transport network system, and many traders remain.